2012
DOI: 10.1016/j.neuroimage.2011.06.037
|View full text |Cite
|
Sign up to set email alerts
|

A selective review of simulated driving studies: Combining naturalistic and hybrid paradigms, analysis approaches, and future directions

Abstract: Naturalistic paradigms such as movie watching or simulated driving that mimic closely real-world complex activities are becoming more widely used in functional magnetic resonance imaging (fMRI) studies both because of their ability to robustly stimulate brain connectivity and the availability of analysis methods which are able to capitalize on connectivity within and among intrinsic brain networks identified both during a task and in resting fMRI data. In this paper we review over a decade of work from our gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
74
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(75 citation statements)
references
References 75 publications
1
74
0
Order By: Relevance
“…Experimental studies have demonstrated that increased blood alcohol concentration (BAC) impairs cognitive functioning such as motor control, judgement and alertness in a dose-dependent manner, and because alcohol is metabolized at a constant rate, the risk of injury is likely to be highest during the period before BAC level drops below the low risk level (e.g. legal limit for driving) [1][2][3]. Many emergency department studies and several meta-analyses have also concluded that exposure to alcohol substantially increases the risk of injury -particularly injuries occurring within 6 h of exposure to alcohol [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Experimental studies have demonstrated that increased blood alcohol concentration (BAC) impairs cognitive functioning such as motor control, judgement and alertness in a dose-dependent manner, and because alcohol is metabolized at a constant rate, the risk of injury is likely to be highest during the period before BAC level drops below the low risk level (e.g. legal limit for driving) [1][2][3]. Many emergency department studies and several meta-analyses have also concluded that exposure to alcohol substantially increases the risk of injury -particularly injuries occurring within 6 h of exposure to alcohol [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Together, these findings have demonstrated that virtual reality technology allows simulations of driving tasks that would be impractical, dangerous, unethical, or even impossible in real contexts and enables the measurement of brain function during simulated driving [60].…”
Section: Car Drivingmentioning
confidence: 86%
“…In [5], the relatively new approach of using noninvasive brain stimulation technologies presented does not preclude the further investigation of applied science questions. Rather, brain stimulation for the sake of cognitive enhancement in "normal" subjects expands the domain, applicability, development, and understanding of traditional stimulation research.…”
Section: By Combining Real-time Fmri Monitoring and Neuro Feedback Dumentioning
confidence: 99%
“…According to [5,6], Naturalistic paradigms such as movie watching or simulated driving that mimic closely real-world complex activities are becoming more widely used in functional magnetic resonance imaging (fMRI) studies both because of their ability to robustly stimulate brain connectivity and the availability of analysis methods which are able to capitalize on connectivity within and among intrinsic brain networks identified both during a task and in resting fMRI data.…”
Section: By Combining Real-time Fmri Monitoring and Neuro Feedback Dumentioning
confidence: 99%